A Novel Selective and Sensitive Electrochemical Sensor for Insulin Detection - Zulkarnain Zulkarnain; Suprapto Suprapto; Taslim Ersam; Fredy Kurniawan (Institute of Advanced Engineering and Science, 2016)
A novel selective and sensitive electrochemical sensor for insulin detection has been fabricated and investigated. The electrochemical sensor was made from a mixture of silica gel, chitosan and nickel hydroxide (Ni(OH)2) nanoparticles, which was mounted on a silver wire and covered by a glass tube (silica gel/chitosan/Ni(OH)2 nanoparticles paste electrode). The sensor was characterized using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The anodic and cathodic currents of the silica gel/chitosan paste electrode with Ni(OH)2 are 580 mA and -750 mA, respectively. Without Ni(OH)2, however, the currents are 150 mA and -250 mA, respectively. The sensitivity and limit of detection of the silica gel/chitosan/Ni(OH)2 nanoparticle paste electrode for insulin detection are 5573 × 105pA/pMcm2 and 0.25 pM, respectively. The sensor also shows good reproducibility of measurement for 35 days with an RSD of 0.29%. The fabricated electrodes also show good reproducibility, with an RSD of 1.39%.